Effects of music during exercise on RPE, heart rate and the autonomic nervous system - Yamashita, S.; Iwai, K.; Akimoto, T.; Sugawara, J.; Kono, I. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The purpose of this study was to investigate the relationship between the influence of music on RPE during sub-maximal exercise and on the autonomic nervous system before and after sub-maximal exercise. Methods: Heart rate (HR), HR variability (HRV) and rates of physical fatigue (RPE) during exercise at 60% and at 40% V.O2max with and without music were measured. The exercise protocol consisted of a 30-min seated rest (control) period followed by a 30-min submaximal cycling exercise and a 35-min recovery period. Autonomic-nervous activity was measured before and after exercise. During exercise, RPE was recorded every 3 min and HR was recorded for every minute. Results: Although RPE did not differ during exercise at 60% V.O2max, this value was lower during exercise at 40% V.O2max in the presence, than in the absence of a favorite piece music (P<0.05). HR, HFA and LFA/HFA of HRV significantly differed with exercise intensity in the absence (P<0.05), but not in the presence of music. Conclusions: These findings suggested that music evokes a ''distraction effect'' during low intensity exercise, but might not influence the autonomic nervous system. Therefore, when jogging or walking at comparatively low exercise intensity, listening to a favorite piece of music might decrease the influence of stress caused by fatigue, thus increasing the ''comfort'' level of performing the exercise.